2020
DOI: 10.1182/blood-2020-136258
|View full text |Cite
|
Sign up to set email alerts
|

Discordances between Immunofixation (IFx) and Minimal Residual Disease (MRD) Assessment with Next-Generation Flow (NGF) and Sequencing (NGS) in Patients (Pts) with Multiple Myeloma (MM): Clinical and Pathogenic Significance

Abstract: Background: Previous studies showed that MRD- pts after transplant may have detectable monoclonal protein through IFx, creating confusion regarding their prognostication. That said, MRD assessment in these pts was not performed with next generation techniques nor or in later time points. Additional discordances have been identified between multiparameter flow cytometry (MFC) and NGS, which were confirmed in recent analyses comparing NGF vs NGS. Aim: To characterize discordances between flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…An analysis of patients MRD-negative by NGF enrolled in 2 Spanish trials showed that 11% of them still had positive serum immunofixation. Remarkably, similar PFS rates were observed in these patients, as compared with MRD-negative/immunofixation-negative patients (4-year PFS 87% vs. 78.5%, P = 0.35) 61 …”
Section: Should Mrd Be Used As a Surrogate For Survival?supporting
confidence: 68%
See 1 more Smart Citation
“…An analysis of patients MRD-negative by NGF enrolled in 2 Spanish trials showed that 11% of them still had positive serum immunofixation. Remarkably, similar PFS rates were observed in these patients, as compared with MRD-negative/immunofixation-negative patients (4-year PFS 87% vs. 78.5%, P = 0.35) 61 …”
Section: Should Mrd Be Used As a Surrogate For Survival?supporting
confidence: 68%
“…Remarkably, similar PFS rates were observed in these patients, as compared with MRD-negative/immunofixationnegative patients (4-year PFS 87% vs. 78.5%, P = 0.35). 61 Finally, several studies demonstrated the prognostic role of metabolic response by PET/CT on outcome. Moreau and colleagues 62 showed that the normalization of PET/CT before maintenance treatment was predictive of improved PFS (2-year PFS 72% vs. 57%, P = 0.01) and OS (2-year OS 94% vs. 73%, P = 0.03), as compared with the persistence of PET/CT positivity.…”
Section: Should Mrd Be Used As a Surrogate For Survival?mentioning
confidence: 99%
“…It is plausible, however, that these patients had a stable residual MRD clone with no clinical consequences (immune equilibrium) akin to the subset with MRD conversion, but without clinical relapse 28,48,49 . In addition, in such cases deeper testing detected immature clonotypic cells that lacked most somatic mutations and copy number variation found in myeloma plasma cells and thus were unable to drive disease relapse 50 .…”
Section: Discussionmentioning
confidence: 99%
“… 27,47,48 In addition, in such cases, deeper testing detected immature clonotypic cells that lacked most somatic mutations and copy number variation found in myeloma plasma cells and thus were unable to drive disease relapse. 49 …”
Section: Discussionmentioning
confidence: 99%